Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Belanja Modal di Jawa Tengah (2020-2023) - Novalia Salma Putri; Nursiam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine and analyze the effect of Regional Original Income (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK) on Capital Expenditure in Regencies/Cities in Central Java Province during the 2020-2023 period. A descriptive quantitative approach with purposive sampling technique was used in this study, resulting in 35 samples obtained 140 data. Data were obtained from official government sources djpk.kemenkeu and analyzed using multiple linear regression, with classical assumption test to ensure model reliability. The results showed that PAD has a positive effect on capital expenditure, indicating that the higher the regional income, the greater the allocation of capital expenditure. Likewise, DAK has a positive impact, indicating that special funds allocated to certain sectors contribute to increasing capital expenditure. However, DAU does not have a significant effect on Capital Expenditure, indicating that general allocation funds do not directly encourage capital expenditure allocation.